Altered Loyalties of Neuronal Markers in Cultured Slices of Resected Human Brain Tissue. (7th December 2015) - Verwer, Ronald W. H.; Sluiter, Arja A.; Balesar, Rawien A.; Baayen, Johannes C.; Speijer, Dave; Idema, Sander; Swaab, Dick F.
Abstract: Organotypic cultures from normal neocortical tissue obtained at epilepsy surgery show a severe injury response. This response involves both neuronal degeneration and the proliferation of reactive cells. A salient feature of the reactive cells is the co‐expression of microglial and astrocytic markers. Surprisingly, the reactive cells also began to express neuronal markers Tubulin βIII and MAP2 adding to the confusion about their origin. Concomitant with their appearance in reactive cells MAP2 and Tubulin βIII expression disappeared from neurons. While NeuN expression decreased significantly, it did not entirely disappear from many neurons. Moreover, it was not observed in reactive cells, showing that NeuN is a reliable marker of neurons.